Perbedaan Parameter Eritrosit Dan Retikulosit Pada Pasien Talasemia Beta Minor Dan Anemia Defisiensi Besi Ringan - Roes, Bellya Affan; Prihatni, Delita; Tristina, Nina (Indonesian Journal of Health Science, 2024)
Beta thalassemia and iron deficiency anemia (IDA) are most common microcytic hypochromic anemia. It is difficult to distinguish minor β thalassemia from mild iron deficiency anemia only by clinical findings and routine hematology examinations, it requires confirmatory tests which are limited in availability and relatively expensive. The presence of additional erythrocyte and reticulocyte parameters (RDW-CV, RBC-He, %MicroR, %Hypo-He, Ret-He, IRF) in hematology analysers are expected to be screening parameters in differentiating minor β thalassemia from mild IDA. The purpose of this study was to determine the differences in the values ​​of RDW-CV, RBC-He, %MicroR, %Hypo-He, Ret-He, and IRF between minor β thalassemia patients and mild IDA.              This study was an observational, analytical, comparative, with a cross sectional design. Research was conducted at RSU Kota Tangerang Selatan from July to October 2020. Subjects were children who went to an outpatient clinic/medical check-up, or with laboratory data of minor β thalassemia or had β thalassemia families. Samples were analysed using Sysmex XN 1000. Statistical analysis was performed by the independent t test for normally distributed data and the Mann Whitney difference test for abnormally distributed data.     The RBC-He and Ret-He values ​​were lower in minor β thalassemia than mild IDA and significantly different with p value 0.005 and 0.004, respectively. The %MicroR and %Hypo-He values were higher in minor β thalassemia than mild IDA and significantly different with p values ​ 0.000 and 0.003, respectively. The RDW-CV and IRF values ​​were higher in minor β thalassemia than mild IDA but were not significantly different with the p value 0.076 and 0.528 respectively.     Conclusion: RBC-He and Ret-He values which reflect hemoglobin content in erythrocytes and reticulocytes ​​were lower in minor β thalassemia patients compared to mild IDA and were significantly different. The values ​​of %MicroR and %Hypo-He which reflect microcytic and hypochromic in erythrocyte population were higher in patients with minor β thalassemia than mild IDA and were significantly different. RDW-CV which reflects variation size of erythrocytes and IRF which reflects erythropoiesis activity and ineffective erythropoiesis were higher in patients with minor β thalassemia than mild IDA and were not significantly different.